1984
DOI: 10.1136/adc.59.11.1052
|View full text |Cite
|
Sign up to set email alerts
|

Maternal drug histories and central nervous system anomalies.

Abstract: SUMMARY Prescription data for the three months before the last menstrual period and for the first trimester of pregnancy were obtained for 764 mothers whose children had a defect of the central nervous system and for an equal number of mothers of control babies born from the same doctors' practices. There was a statistically significant difference overall between the numbers of mothers who were prescribed drugs in the study and control groups during the trimester before the last menstrual period but no such di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 26 publications
(1 reference statement)
1
17
0
Order By: Relevance
“…Congenital malformations of various types have been associated with DB ingestion in early pregnancy (Donnai & Harris, 1978;Rothman et al, 1979) but the results of large prospective cohort studies have failed to produce any evidence that DB is teratogenic in humans (Correy & Newman, 1971;Milkovich & van den Berg, 1976;Shapiro et al, 1977;Smithells & Sheppard, 1978;Harron et al, 1980;Gibson et al, 1981;Jick et al, 1981). Case control studies have supported these findings (Winship et al, 1984). A literature review by MacMahon (MacMahon, 1981) suggests that although a causal association of DB and malformations can never be absolutely denied, evidence indicates that any teratogenic potential is only rarely expressed.…”
Section: Discussionsupporting
confidence: 58%
“…Congenital malformations of various types have been associated with DB ingestion in early pregnancy (Donnai & Harris, 1978;Rothman et al, 1979) but the results of large prospective cohort studies have failed to produce any evidence that DB is teratogenic in humans (Correy & Newman, 1971;Milkovich & van den Berg, 1976;Shapiro et al, 1977;Smithells & Sheppard, 1978;Harron et al, 1980;Gibson et al, 1981;Jick et al, 1981). Case control studies have supported these findings (Winship et al, 1984). A literature review by MacMahon (MacMahon, 1981) suggests that although a causal association of DB and malformations can never be absolutely denied, evidence indicates that any teratogenic potential is only rarely expressed.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, women who started the use of supplements after conception seem to be classi®ed as`non-users' (Mills et al, 1989), whereas other observational studies have indicated that folic acid can also be protective in this period (Milunsky et al, 1989;Bower & Stanley, 1989;Shaw et al, 1995). Other reasons could be the broad range of central nervous system defects that were included as cases in both studies (Winship et al, 1984;Mills et al, 1989).…”
Section: Developments Regarding Folate Requirementsmentioning
confidence: 87%
“…In two case-control studies the reduction in the risk of an NTD-affected birth was not signi®cant (Winship et al, 1984;Mills et al, 1989). The study of Winship et al, (1984) lacked information on the use of non-prescribed drugs (of which folic acid is a common one) and on the use of drugs prescribed by hospital physicians.…”
Section: Developments Regarding Folate Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete list of excluded studies is available from the authors. Thirteen studies that examined major malformations, 11 13 14 23 – 32 11 studies that examined oral cleft alone, 1 7 10 13 27 30 31 33 – 36 and three studies that examined other specific malformations3739 were included (some providing information for more than one evaluation). One study unpublished at the time of consideration has since been published 26…”
Section: Introductionmentioning
confidence: 99%